Toward Sustainable Wellbeing: Advances in Contemporary Concepts - O'Mahony, Tadhg (Frontiers in Sustainability, 2022)
Sustainability and wellbeing are two key global policy priorities, which despite considerable overlap, are invariably isolated. In wellbeing, the importance of social dimensions is an emergent conclusion, but recognition of the environment and nature is embryonic. In sustainability, wellbeing remains poorly characterised. Despite some procedural advantages, in practice, a continued ambiguity risks compromising both goals, and improved conceptual integration is therefore necessary. In this review article, key contemporary wellbeing accounts are considered, including preferences, needs, capabilities, happiness, psychological wellbeing and physical wellness. Wellbeing literature suggests that a holistic multidimensional account is strongly supported, that is context- and value-dependent, with a prominent role for social and relational dimensions. A transdisciplinary systems thinking approach is appropriate to integrate from the individualism characteristic of wellbeing, to the interdependent human and environmental systems of sustainability. It is recognised that both wellbeing and sustainability are complex and value-laden, requiring the surfacing of values and ethics. A synthesis of the two branches of literature asserts four fundamental lenses: the framing of growth and change; social justice; the ethics of freedom; and the value of nature. The conceptual synthesis both platforms the relational approach of ‘care,’ and underlines the imperative to reconsider the place of consumption. An integrated ‘sustainable wellbeing’ offers the potential for win-win outcomes, in transformation to a flourishing of human wellbeing and the natural world.